The Maintenance Process Improvement of Radiological Health Equipment, by Utilizing Internet of Things (IoT) - Z J Azra, M Dachyar (International Journal of Advanced Science and Technology, 2020)
Hospitals must ensure that their medical devices are safe, accurate, reliable, andcomply with a particular level of performance. Taking one private hospital in Indonesiaas a research object, in radiology, the conventional X-ray and Panoramic devices are thehighest usage equipment. Proper maintenance should be done to avoid any possiblebreakdown. The process of maintaining medical equipment adopted by the hospital iscurrently 37,41% consist of manual administration (paperwork) and only 54,04% ofactual inspection and maintenance activities. This research aims to improve themaintenance process of conventional X-rays and panoramic devices, by utilizing theInternet of Things (IoT). Business Process Reengineering (BPR) is used to rectify thehealth equipment maintenance process. The information system is proposed to themaintenance process using Data Flow Diagram (DFD). This research recommends fourmaintenance process improvement options, where the highest time efficiency is 56.25%,which is generated by the selection improvement “intervention of ComputerizedMaintenance Management System (CMMS) software, integrated QR Code and radiofrequency Identification (RFID) tags, and condition-based monitoringtechnology/sensor”.